KAJIAN PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA FAKULTAS ILMU TARBIYAH DAN KEGURUAN IAIN WALISONGO SEMARANG - Hashona, Achmad Hasmi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: FieldExperience Practice (PPL) is programmed activity to student as educator candidate in school activity both in and outside class. PPL as sharpen media to studentteaching ability, in order to apply science which have been obtained bylearning in the education program. In line with target of education, Faculty Science of Tarbiyah and Teacher ship, representing one of the faculty in IAIN Walisongo Semarangenvironment, aim to develop competence and improve professionalism in the field of Islamic Education, which consist of Education Of Islamic Religion (PAI), Education Of Language Arab (PBA), Islamic Education (KI) and Tadris MIPA (Education Of Mathematics, Education Of Biology, Education Of Chemistry, Education of Physics and Education of English).This solution focused to study execution of PPL in Faculty Science of Tarbiyah and Teacher ship of IAIN Walisongo Semarang which practice at Madrasa and expected can give idea contribution and policy to improve and repair pattern of PPL with good quality and give many benefit not only for student of practical, but also for the Institute and progress of education itself.Â Ø§ÙØªØ¹ÙÙÙ Ø£ÙØ´Ø·Ø© ÙÙ Ø§ÙÙØØªÙÙÙÙ ÙÙØ¹ÙÙÙÙ ÙÙØ·ÙØ§Ø¨ Ø§ÙÙØ¨Ø±ÙØ¬Ø© Ø§ÙØ£ÙØ´Ø·Ø© ÙÙ Ø³ÙØ³ÙØ© Ø¹Ù Ø¹Ø¨Ø§Ø±Ø© )PPL( ÙÙ Ø§ÙÙÙØ§Ø±Ø³Ø© ØªØ¬Ø±Ø¨Ø©Â ÙØ±Ø®Ø£ Ø©Ø±Ø§Ø¨Ø¹Ø¨Ù ØØ§ÙØªØ¯Ø±ÙØ³ ÙÙØ§Ø±Ø³Ø©Â  ÙÙ ÙØ¯Ø±Ø§ØªÙÙÂ  ÙÙØµÙÂ  ÙÙØ·ÙØ§Ø¨ ÙØ³ÙÙØ©Â  PPL ÙÙÂ  .Ø§ÙØ¯Ø±Ø§Ø³ÙØ©Â  Ø§ÙÙØµÙÙÂ  ÙØ®Ø§Ø±Ø¬Â  Ø¯Ø§Ø®Ù ÙØ§ÙØªØ¹ÙÙÂ ÙØªÙØ´ÙØ§Â  .Ø§ÙØªØ¹ÙÙÙÙØ©Â  Ø§ÙØ¨Ø±Ø§ÙØ¬Â  ÙÙÂ  Ø¥ÙØ²Ø§ÙÙØ©Â  ÙÙØ§Ø¯Ø©Â  ÙÙØ§Ø±Ø³Ø©Â  Ø³ÙØ¨ Ø§ÙÙÙÙØ©Â  ÙÙÂ  Ø§ÙÙØØ§Ø¶Ø±Ø§Øª Ø®ÙØ§ÙÂ  Ø§ÙØªØ³Ø§Ø¨ÙØ§Â  ØªÙÂ  Ø§ÙØªÙ Ø§ÙÙØ¹Ø±ÙØ©Â  ÙØªØ·Ø¨ÙÙÂ ÙØ¥Ø¹Ø¯Ø§Ø¯Â  ÙØ¯ÙÙ ÙØ°ÙØ§Ù ØÙÙÂ  Walisongo IAIN Ø³ÙÙØ§Ø±Ø§ÙØ¬ Ø§ÙÙÙÙØ§Øª ÙÙ ÙØ§ØØ¯Ø©Â  ÙÙ ØÙØ§ÙØªØ¹ÙÙÙÂ  Ø©ÙÙÙ ØØ§ÙØªØ±Ø¨ÙØ©Â  Ø£ÙØ¯Ø§Ù ÙØ¹Â  )Ø§Ø¨Ø¨)Â  Ø§ÙØªØ¹ÙÙÙÂ  Ø©ÙØ¨Ø±Ø¹ÙØ§ Ø§ÙØ¥Ø³ÙØ§ÙÙØ©Â  Ø§ÙØªØ±Ø¨ÙØ©Â  ÙÙÂ  ØªØªØ£ÙÙ Ø§ÙØªÙ ØØ§ÙØ¥Ø³ÙØ§ÙÙ Ø§ÙØªØ¹ÙÙÙÂ  ÙØ¬Ø§ÙÂ  ÙÙ ÙØ§ØªØ±ØÙØ§Ø§ÙÂ  Ø§ÙÙÙØ§Ø¡Ø©Â  Ø²ÙØ²Ø¹ØªÙÂ  Ø§ÙØ®Ø¨Ø±Ø§Ø¡Â ÙØ§ÙØ¥ÙØ¬ÙÙØ²ÙØ©Â  Ø©ÙÙØ¯Ø¨ÙØ§ Ø©ÙØ¨ØªØ±ÙØ§Ù ØØ§ÙØªØ¹ÙÙÙÂ  Ø¡Ø§ÙÙÙÙÙØ§ ØØ§ÙØ£ØÙØ§Ø¡Â  Ø¹ÙÙÂ  ÙØ§ÙØªØ¹ÙÙÙÂ  Ø§ÙØªØ±Ø¨ÙØ©Â  )Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙØ§ÙØ±ÙØ§Ø¶ÙØ§Øª Ø§ÙØ¥Ø³ÙØ§ÙÙØ©Â  Ø§ÙØªØ±Ø¨ÙØ©Â ÙÙØ§Ø±Ø³Ø© ÙÙ IAIN Walisongo ØªØ¹ÙÙÂ  ÙÙÙØ© ÙØ§ÙØªØ¹ÙÙÙÂ  ÙØ·Ø§Ù PPL ÙÙÂ  ØªÙÙÙØ° ØªÙÙÙÙ Ø¹ÙÙ Ø§ÙÙÙØ§ÙØ´Ø© ÙØ°Ù Ø§ÙØªØ¹ÙÙÙ(. ÙØªØ±ÙØ²Â ÙÙØ³ Ø§ÙÙÙØ§Ø¦Ø¯Â  ÙÙ Ø§ÙØ¹Ø¯ÙØ¯Â  ÙØªÙÙÙØ± Ø£ÙÙØ§Ø· ÙÙØ¹ÙØ©Â  ÙÙØ³ØªØ ÙÙØ¥ Ø©ÙÙØ§Ø±ÙØ§ ØªØ§Ø³Ø§ÙØ³ÙØ§ÙÂ  Ø§ÙØ£ÙÙØ§Ø±Â  ØªØ³ÙÙÂ  ÙØ£ Ø¹ÙÙØªÙÙÂ  Ø§ÙØ¯ÙÙÙØ©Â  Ø§ÙÙØ¯Ø§Ø±Ø³.Ø¨Ø§ÙØªØ¹ÙÙÙÂ  Ø§ÙÙÙÙØ¶ ÙÂ  ÙÙÙØ¹ÙØ¯Â  ÙÙÙÙ ØØ·Ø§ÙØ¨ Ø³Ø±Ø§ÙÙÙ ÙÙØ·